The early Eocene Eourocerus anguliterreus gen. et sp. nov (Hymenoptera, Siricidae) from Republic, Washington - Archibald, S.b.; Rasnitsyn, A.p. (Zootaxa, 2022)
A new fossil horntail wood wasp (Hymenoptera, Symphyta, Siricidae), Eourocerus anguliterreus gen. et sp. nov. from an early Eocene Okanagan Highlands locality at Republic, Washington, USA is described. Its forewing is most like that of the extant and fossil genus Urocerus Geoffroy, 1785. It is the third fossil siricid described from North America. We treat Xeris dorbnikensis Manukyan & Smirnova, 2021 and Xeris sp. of Manukyan & Smirnova (2021) as Urocerus dorbnikensis (Manukyan & Smirnova, 2021), comb. nov. and Urocerus sp., both tentatively belonging to the genus, Urocerus klebsi Brues, 1926 as Xeris klebsi (Brues, 1926) comb. nov., and “Afrotremex or Eriotremex sp.” of Wedmann (1998) as a species of Eriotremex Benson, 1943. A key to extant and extinct genera of Siricinae by forewing characters is given.